What is the evidence-base for climate-smart agriculture in Malawi? An analysis of what works where powered by Evidence for Resilient Agriculture (ERA) - Steward, Peter R.; Nyoka, Isaac; Lamanna, Christine; Kamau, Hannah N.; Namoi, Nictor; Nowak, Andreea C.; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Agriculture drives Malawi’s economy. This sector accounts for 30% of Gross Domestic Product (GDP), generates more than 80% of the national export earnings and employs 64% of the country's workforce. This productivity results in large part from the actions of smallholder farmers, which generate 70% of the economic agricultural value in the country. Much of this productivity is from maize, which covers about 50% of the total cultivated land in Malawi and is grown by 97% of farmers. Other major food crops include cassava, rice, sorghum, sweet potato, beans, groundnuts and pigeon pea.